An Effective Heterogeneous Ozone-Based Advanced Oxidation Process in Acidic Solution— Ti-MCM-41/H2O2/O3. (3rd May 2016) - Peng, Ruofan; Shen, Tongdong; Tong, Shaoping; Ma, Chunan
ABSTRACT: A useful ozone-based advanced oxidation process in acidic solution- Ti-MCM-41/H2 O2 /O3 was studied, and acetic acid (HAc) was selected to be degraded because it is a hydroxyl radical-probe compound in ozonation. The results showed that only Ti-MCM-41/H2 O2 /O3 could effectively degrade HAc at initial pH 3.0, and that other oxidative processes such as O3, H2 O2 /O3 Ti-MCM-41/O3 and MCM-41/H2 O2 /O3, all could not, indicating the coexistence of Ti-MCM-41 and H2 O2 was necessary for the generation of hydroxyl radicals under the experimental conditions. The optimization of parameters indicated that the rate of generation of hydroxyl radicals could be regulated by the amount of Ti-MCM-41, and that the amount of hydroxyl radicals could be controlled by the concentration of H2 O2 . The preceding results are of significance for effective treatment of acidic refractory wastewater.